Time series analysis of the impact of air pollutants on influenza-like illness in Changchun, China - Yang Pan; Laishun Yao; Biao Huang; Yinghua He; Changxi Xu; Xianda Yang; Yingying Ma; Zhidi Wang; Xingyu Wang; Hong Zhu; Man Wang; Lijun Song; et al. (BMC Public Health)
Abstract Background Emerging evidence links air pollution to respiratory infections, yet systematic assessments in cold regions remain limited. This study evaluates the short-term effects of six major air pollutants on influenza-like illness (ILI) incidence in Changchun, Northeast China, with implications for air quality management and respiratory disease prevention. Methods ILI surveillance data from Changchun were extracted from “China Influenza Surveillance Network” and the ambient air quality monitoring data of the city were collected from 2017 to 2022. A generalized additive model (GAM) with quasi-Poisson regression analysis was employed to quantify pollutant-ILI associations, adjusting for meteorological factors and temporal trends. Results Among 84,010 ILI cases, immediate exposure effects were observed: each 10 µg/m³ increase in PM2.5 (ER = 1.00%, 95% CI: 0.63–1.37%), PM10 (0.90%, 0.57–1.24%), and O3 (1.05%, 0.44–1.67%) significantly elevated ILI risks. Young and middle-aged individuals (25–59 years old) exhibited the highest susceptibility to five pollutants (PM2.5, PM10, SO2, O3, and CO), and age subgroups under 15 years old exhibited susceptibility to NO2. Post-COVID-19 outbreak showed amplified effects across all pollutants (p < 0.05 vs. pre-outbreak). The effects of PM2.5, PM10, SO2 and O3 on ILI cases were greater in the cold season (October to March) (p < 0.05). Conclusions PM2.5, PM10, and O3 exposure significantly increases ILI risks in Changchun, particularly among young/middle-aged populations during cold seasons and post-pandemic periods. These findings underscore the urgency for real-time air quality alerts and targeted protection strategies during high-risk periods to mitigate respiratory health burdens.